HUBUNGAN FUNGSI KEPEMIMPINAN DAN MOTIVASI KARYAWAN TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT JIWA DAERAH DR. AMINO GONDOHUTOMO SEMARANG - Roy Bagus Royyani; Drs. Wiwid Noor Rakhmad, M.I.Kom (Interaksi Online, 2017)
Communications committed to leadership and motivation of subordinates who provided the leadership to the subordinate is essential in the achievement of the objectives of the institution or organization, so as to increase the job satisfaction of subordinates, who were later promoted to the discipline and their work. This also applies at Regional psychiatric hospital Dr. Amino Gondohutomo Semarang. Note that never happened because the employee demo leadership there is no transparency regarding the recruitment of manpower from BLUD demo several times occurred in 2008, 2010, and 2011. Then the leader should always attempt to direct, motivate them and behave as well as possible, so that their efforts can increase the individual satisfaction of his subordinates. The theory used in this research there are three, namely (1) transformational leadership theory , (2) Theory of hierarchy, and (3) a theory of Justice (Equity Theory). This research is a explanatory research that will explain the relationships between variables. The sample of this research is the mental hospital employee Area of Dr. Amino Gondohutomo Semarang, with the number of respondents i.e. 100 people that is divided into two, the nurse (medical) employees and non-medical employees. The analysis of the data used is cross-table test, test the correlation of spearman rho, and test the R Square. Hypothesis test results found that the leadership function variables have a strong link between employee job satisfaction, variable with the value of the coefficient of correlation with the level correlation 0.48 strong relationships. When both variables are functions of leadership and employee job satisfaction variables controlled with variable motivations of employees found that the original function of the leadership has strong relationships with employee job satisfaction, the relationship becomes weak. This means that functions that do the leadership is very high but employee motivation is weak, this making the job satisfaction of employees owned employees become weak. Overall job satisfaction not only can be measured from effectively functions done leadership but employee motivation can give impact on the level of job satisfaction of employees. That generates the view that to improve employee job satisfaction not only of effectively functions done leadership but also need to see from employee motivation, since employee motivation also has a large role towards increasing employee satisfaction.